The competency-based approach in developing countries - (:unkn) unknown (My University, 2013)
For decades, all analyzes converge on the idea of the relative inefficiency of education systems in sub-Saharan Africa. Dropout, repetition, overstaffing, low quality of learning student failure and obsolescence of facilities, teaching materials and teachers, including sometimes the levels and quality of education remain somewhat uncertain, inadequate educational programs. In short, these are some of the ills that plague these systems and confirm the findings made by many reports.Given this weakness finding, educational authorities, supported by international aid mobilized in many countries to improve their systems to qualitatively, but also quantitatively equity because we must not forget in these systems, the structural and contextual dimorphism makes them highly unequal. Faced with this crisis, one of the interviews solutions with short and medium-term effects has been to fundamentally rethink the curriculum. In this context, the competencies approach constitutes one of the major developments in educational research of the past three decades, was selected as most suitable to meet the basic educational needs of school populations.To define its contours and appreciate the merits, an objective analysis of the results of these reforms, some of which began in 1998 was necessary. Thus, this research aims to assess both the relevance that the level of effectiveness of curricular reforms implemented in three Francophone African countries namely: Benin, Gabon and Madagascar. Drawing on data from the educational systems analysis program in Francophone Africa (PASEC) and an ad hoc survey in Gabon, the study attempts to identify the determinants of educational effectiveness from the comparative performance analysis and a sequential study of teaching practices. If the results come out real transformations from the perspective of teaching practices, school performance indicators are in turn quite disappointing. However, with major support measures what initiated
Keywords: African Research